Mental health and attitudes toward suicide amongst individuals with gender dysphoria in Iran - Assareh, Maryam; Rashedi, Vahid; Eftekhar Ardebili, Mehrdad; Salehian, Razieh; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2024)
IntroductionGender dysphoria (GD) is associated with profound mental health challenges, including heightened suicide risk. This study aimed to explore the mental health status and attitudes toward suicide among individuals with GD in Iran.MethodsA comprehensive assessment was conducted using three validated tools: the General Health Questionnaire (GHQ-28) to gauge emotional distress and psychological well-being, the Beck Depression Inventory (BDI-II) to evaluate the severity of depressive symptoms, and the Predicament Questionnaire (PQ) to measure attitudes toward suicide in the context of social crises.ResultsAmong the 78 participants, 43 (55.1%) were identified as experiencing significant mental health issues, while 21 (26.9%) were found to suffer from severe depression. The average PQ score was 57.92, which aligns with findings from similar populations in previous studies, highlighting a concerning trend in suicide-related attitudes. Further statistical analysis revealed significant correlations between psychological distress (GHQ-28 scores) and attitudes toward suicide (PQ scores), as well as between depressive symptoms (BDI-II scores) and suicide-related attitudes.ConclusionsThese findings indicate a pervasive prevalence of psychological disorders, particularly depression, within this group, and underscore the strong association between depressive states and suicidal ideation. The study underscores the urgent need for targeted mental health interventions and comprehensive healthcare policies tailored to the specific needs of individuals with GD in Iran. Given the substantial mental health burden observed, particularly the risk of suicide, this research highlights the critical importance of integrating mental health care into broader support systems for this population.